Jaguar Panthera onca population decline in the Upper Paraná Atlantic Forest of Argentina and Brazil - Paviolo, Agustin Javier (2008)
The Green Corridor of Argentina and Brazil is the largest forest remnant of the Upper Paraná Atlantic Forest. The jaguar population of this region is highly fragmented and reduced. To assess the status of the subpopulation of jaguars of the Green Corridor we conducted four camera-trap surveys in three sites with different levels of protection. At Urugua-í (34 stations, 1,495 trap-days) we recorded one individual (minimum density = 0.12-0.33 per 100 km2). At Yabotí Biosphere Reserve (42 stations, 1,871 trap-days) we recorded two individuals (minimum density = 0.11-0.25 per 100 km2). At Iguazú National Park we conducted two surveys. In 2004 (39 stations, 1,839 trap-days) we recorded four adult individuals, estimating a density of between 0.49 ± 0.16 and 1.07 ± 0.33 per 100 km2. In 2006, we increased the area sampled (47 stations, 2,059 trap-days) and recorded 11 adult individuals, estimating a density of 0.93 ± 0.2 to 1.74 ± 0.34 per 100 km2. These density estimates are the lowest recorded for the species. Estimates for Iguazú are between 2-7.5 times lower than those reported in the early 1990s. This population decline probably results from the interaction of several factors, including lack of prey as a result of poaching and persecution. We estimate that there is currently a population of 25-53 adult jaguars in the Green Corridor. In spite of having sufficient potential habitat available this population is threatened and urgent conservation action is required. © 2008 Fauna & Flora International.